2021
DOI: 10.1021/acs.jpclett.1c01411
|View full text |Cite
|
Sign up to set email alerts
|

Generating Triplets in Organic Semiconductor Tetracene upon Photoexcitation of Transition Metal Dichalcogenide ReS2

Abstract: We studied the dynamics of transfer of photoexcited electronic states in a bilayer of the two-dimensional transition metal dichalcogenide ReS 2 and tetracene, with the aim to produce triplets in the latter. This material combination was used as the band gap of ReS 2 (1.5 eV) is slightly larger than the triplet energy of tetracene (1.25 eV). Using time-resolved optical absorption spectroscopy, transfer of photoexcited states from ReS 2 to trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…24−26 An in-depth study of the synthesis of crystalline few-layered ReS 2 flakes through liquid-phase exfoliation has been reported recently, and first reports indicate their promising potential for PV applications. 27,28 Although high-quality ReS 2 nanoflakes obtained through such exfoliation procedures are clearly promising materials, the nature and dynamics of elementary optical excitations in these novel materials are not yet known, limiting their potential use in applications such as light emission or photovoltaics.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24−26 An in-depth study of the synthesis of crystalline few-layered ReS 2 flakes through liquid-phase exfoliation has been reported recently, and first reports indicate their promising potential for PV applications. 27,28 Although high-quality ReS 2 nanoflakes obtained through such exfoliation procedures are clearly promising materials, the nature and dynamics of elementary optical excitations in these novel materials are not yet known, limiting their potential use in applications such as light emission or photovoltaics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similar to other layered semiconductors, ReS 2 can be produced either through vacuum epitaxial growth, exfoliation from high-quality crystals, or direct colloidal synthesis. Exfoliation, particularly through liquid-phase methods, is a cost-effective means to produce flakes of ReS 2 as it combines the advantages of solution processing (low cost and upscaling) while preserving high crystallinity, a persistent issue in direct colloidal synthesis methods. An in-depth study of the synthesis of crystalline few-layered ReS 2 flakes through liquid-phase exfoliation has been reported recently, and first reports indicate their promising potential for PV applications. , Although high-quality ReS 2 nanoflakes obtained through such exfoliation procedures are clearly promising materials, the nature and dynamics of elementary optical excitations in these novel materials are not yet known, limiting their potential use in applications such as light emission or photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Maiti et al demonstrated that 2D ReS 2 with a bandgap energy of 1.5 eV was able to sensitize the triplet state of tetracene (1.25 eV) within 5 ps, thus increasing the triplet quantum yield by up to 38% in tetracene (Figure 7b). [50]…”
Section: D Organic-tmd Heterostructuresmentioning
confidence: 99%
“…Reproduced with permission. [50] 2021, American Chemical Society. (c) Band bending controlled by the thickness of MoS 2 changes the spatial extension of interlayer excitons at the heterojunction with ZnPc.…”
Section: Guidelines For Developing Tmd-based Singlet Fission Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation